2019
DOI: 10.7554/elife.42837
|View full text |Cite
|
Sign up to set email alerts
|

A systematic approach to identify recycling endocytic cargo depending on the GARP complex

Abstract: Proteins and lipids of the plasma membrane underlie constant remodeling via a combination of the secretory- and the endocytic pathway. In the yeast endocytic pathway, cargo is sorted for recycling to the plasma membrane or degradation in vacuoles. Previously we have shown a role for the GARP complex in sphingolipid sorting and homeostasis (Fröhlich et al. 2015). However, the majority of cargo sorted in a GARP dependent process remain largely unknown. Here we use auxin induced degradation of GARP combined with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 59 publications
2
27
0
Order By: Relevance
“…Insulin stimulation mobilizes GSVs to fuse with the PM, but in its continuous presence, GLUT4 molecules are internalized and recycled back to the PM in endosomal vesicles that are distinct from GSVs. Recycling of fungal nutrient transporters has also been reported when growth conditions change ( [76,[80][81][82] and references therein).…”
Section: Endocytosis Of Apical Cargoes and Transporters Occurs By Dismentioning
confidence: 95%
“…Insulin stimulation mobilizes GSVs to fuse with the PM, but in its continuous presence, GLUT4 molecules are internalized and recycled back to the PM in endosomal vesicles that are distinct from GSVs. Recycling of fungal nutrient transporters has also been reported when growth conditions change ( [76,[80][81][82] and references therein).…”
Section: Endocytosis Of Apical Cargoes and Transporters Occurs By Dismentioning
confidence: 95%
“…HPLC analysis was performed on a C30 reversephase column (Thermo Acclaim C30, 2.1 × 250 mm, 3 μm, operated at 50˚C; Thermo Fisher Scientific) connected to an HP 1100 series HPLC (Agilent) HPLC system and a QEx-activePLUS Orbitrap mass spectrometer (Thermo Fisher Scientific) equipped with a heated electrospray ionization (HESI) probe. The analysis was performed as described previously [70]. Peaks were analyzed using the Lipid Search algorithm (MKI, Tokyo, Japan).…”
Section: Plos Geneticsmentioning
confidence: 99%
“…After endocytosis, the cargos recycle back to the tip via the Golgi and the SPK (Hernández-González et al 2018;Casler et al 2019), and results suggest, in both S. cerevisiae and A. nidulans, that this recycling is mediated by the Golgi-Associated Retrograde Protein (GARP) complex. In detail, it was recently shown that Dnf1 and Dnf2 (orthologues of DnfA and DnfB) are substrates of the GARP complex and recycle back to the PM, while their endocytosis requires the AP-2 complex (Eising, Thiele and Fröhlich 2019). Interestingly, the GARP complex also contributes to the recycling of SLs (Fröhlich et al 2015), and consistently SLs are known to be required for polarity maintenance (Cheng et al 2002;Pearson et al 2004;Li et al 2006), probably by promoting the localization of the AP-2 complex in the subapical collar of the hyphae (Fernandes et al 2016;Martzoukou et al 2017).…”
Section: Organization Of Apical Regionsmentioning
confidence: 99%